Pocketbook of orthopaedics and fractures - McRae, Ronald (Churchill Livingstone / Elsevier, 2006)
Thoroughly updated for its Fourth Edition, this pocket-sized go-anywhere Handbook of Fractures is the ideal on-the-spot reference for residents and practitioners seeking fast facts on fracture management and classification. Chapters organized by anatomic site provide key information on fractures in adults and in children, including epidemiology, anatomy, mechanism of injury, clinical evaluation, radiologic evaluation, classification, treatment, and management of complications. The book's easy-access format features numerous charts, tables, diagrams, illustrations, and bulleted lists. This edition includes new and updated information on aspiration of the joints, fracture reduction, traumatic lacerations, and multiple trauma.